The seasons of a restless heart : - Farrington, Debra K. (Jossey-Bass, 2005)
Debra's unique ability to weave personal stories, spiritual reflection and practical suggestions has produced an invaluable aid to assist anyone making an life transition albeit a personal illness, graduation, job change, loss of a love one, divorce or any other crises that befall us in our everyday lives. She speaks as someone who has lived through these dry spells and offers hope for those who cannot see their way clearly that yes there is a tomorrow.